A Literary Study on Paradiguna (Samskara) and its Utility in Clinical Practice - Biswas, Susmita; Sahoo, Manoj Kumar; Das, Arun Kumar; Dasmahapatra, Itishree (International Research Journal of Ayurveda & Yoga, 2023)
The foundation of Ayurveda is its fundamental principles, which are applicable at any time and in any condition. In Ayurveda, one of the Siddhanta that serves as the basis for Dhatusatmya is Sadpadartha. Among the Shatpadhartha, Guna is the most important and basic theory which is useful in clinical practice as well as in research. Among the 41 numbers of Guna, Acharya Charaka has given principle importance of Paradi gunas and these Paradiguna can also be termed as Sidhyupaya chikitsa,” that is, successful management of disease. Paradi gunas play a significant role in the selection, adaptation, and manifestation of drug as per condition of the diseases and the patient, in particular Desha and Kala. There are ten numbers of Paradi guna. Out of these, Samskara Guna is one of them. By utilizing various techniques such as Toya-sannikarsa (adding water), Agni-Sanyoga (lighting a fire), Sodhana (purification), Manthana (churning), Desa (area), Kala (time/season), Vasana (fragrance), and Bhavana (trituration), among others. Physicians and pharmacists use this Samskaraguna to enhance the properties of the drugs.